Economic Dependence as a Criterion for the Protection of the Self-Employed under EU Law and in Selected Member States - Tomasz Duraj (Review of European and Comparative Law)
This paper presents the cornerstones of the conceptual distinctions necessary to map out a separate category of workers, namely “economically dependent self-employed workers” (who fall between dependent subordinated employees and independent self-employed entrepreneurs) from the perspective of the EU law and the laws of selected Member States. The author considers how the economic dependency of self-employed workers should be defined, which method(s) of protection should be applied to these workers, and what scope of protection they should enjoy. The observations in this paper serve as a basis for de lege ferenda recommendations for the Polish legislator. At present, there is no separate category of “economically dependent self-employed workers” in Polish law.